Platelet-derived microparticles during and after acute coronary syndrome - Skeppholm, Mika; Mobarrez, Fariborz; Malmqvist, Karin; Wallén, Håkan (Thrombosis and Haemostasis, 2012)
As microparticles are shedded upon platelet activation, and may be used to assess platelet function, we measured plasma concentrations of platelet-derived microparticles (PMPs) during and after an acute coronary syndrome (ACS). Fifty-one patients with ACS were investigated at admission, within 24 hours (before coronary angiography), and six months later. Sixty-one sex- and age-matched healthy controls were investigated once. PMPs were defined as particles <1.0 μm in size, negative to phalloidin (labels cell-fragments), and positive to CD61. Exposure of phosphatidylserine (PS+), CD62P and CD142 were also measured. Plasma concentrations of PS+PMPs exposing CD61, CD62P and CD142 were elevated 2.5, 6.0-, and 5.0-fold at admission (p<0.001 for all, compared to controls; aspirin only), decreased significantly 24 hours later following initiation of treatment with clopidogrel and subcutaneous anticoagulation (p<0.001 for all), and decreased even further six months later (p<0.01 for all). However, PS+PMPs exposing CD62P or CD142 were still between 1.2-and 2.3-fold higher than in controls (p<0.001 for both). The pattern for PS−PMPs during and after the ACS was very similar to that for PS+PMPs although the numbers were approximately 1/3 lower. In conclusion, PMP concentrations follow the pattern of platelet activation during and after an ACS. Decreased concentrations are observed after initiation of antithrombotic treatment, but PMP exposing CD62P or CD142 are still elevated after six months. Flow cytometric measurements of PMP in frozen-thawed samples enable studies of platelet function in larger clinical trials.
Keywords: Microparticles; tissue factor; P-selectin; phosphatidylserine; ischaemic heart disease